Biodegradation of Polystyrene Waste using Mealworm (Tenebrio molitor) Larvae as a Sustainable Waste Management Approach - Amnan Haris; Yuthika Husnaini Hunafa; Ade Anggun Wana Putri; Olifadia Eka Andiny Aulia; Elvina Afery; Kholimatu Rosita; La Ode rman Jaya (Journal of Environmental and Science Education, 2025)
Styrofoam is widely used as packaging for food, drinks and electronic goods. Usually stirofoam is only used once and thrown away. Styrofoam causes environmental problems, so efforts are needed to degrade it. Using larvae Tenebrio molitor is expected to be an innovative and environmentally friendly solution. The larval stage is used because larvae require large amounts of food for their growth. The larvae's food consists of organic waste such as fruit, vegetables, leaves, rice and others. In fact, stirofoam is considered organic waste because it is made from petroleum which contains hydrocarbons. T. molitor were chosen because they are not consumed by humans. This research aims to analyze the ability of T. molitor to be biodegradation agents for stirofoam. The research stages include cultivating T. molitor for 30 days and analysis which includes viability analysis and larval content using FTIR. The research method used is an experimental method with quantitative data collection. The results of the study showed that even though there was chewing activity, there was no stirofoam content in the bodies of T. molitor.